Usia saat menarche dan usia pertama kali hubungan seksual pranikah wanita dewasa muda di Indonesia: analisis Survei Demografi dan Kesehatan Indonesia 2003-2012 (Berita Kedokteran Masyarakat (BKM), 2018)
Age of menarche and age of premarital sexual young adults Indonesia (Health Demographic Survey data 2003-2012) Purpose: The aim of this study are knowing and analyzing time at menarche with the time at first sexual intercourse of young adult women in Indonesia.Methods: This is a quantitative study using secondary data from Indonesia Health Demographic Survey Data (SDKI) 2003-2012. The number of samples selected in the SDKI 2003 is 523 people, in 2007 that is 2,627 people, and in 2012 that is 2,663 people. The analysis is a survival analysis.Results: The average menarche of adult women in Indonesia in 2003 was 13.67 years, in 2007 that was 13.64 years, and in 2012 that was 13.64 years. The average time of premarital intercourse is around 19 years from 2003 to 2012. The probability to have premarital sexual intercourse in 2003 is 3%, in 2007 is 4%, and on the year 2012 is 4%. In 2007, only external variables are domicile, education and socioeconomic status that have a significant relationship. In the data of SDKI 2012 there is no data that have significant influence on premarital sexual behavior.Conclusions: Young adult women who live in urban areas have a 1.9 chance of having sex faster than young adult women in rural areas. Young adult women with higher education have a probability of 0.51 times faster sexual intercourse in the lower group. In terms of economic status, adult women with upper middle economic status have a chance of 0.3-0.4 times faster sexual intercourse than low socioeconomic status.